THE STUDY OF PROTEIN IN THE COMPOSITION OF AMARANTH FLOUR FROM LOCAL ORIGIN - Akramova Rano Ramizitdinovna; Poziljonova Nodira Nematjon qizi (Journals Park Publishing, 2022)
The present work is the development of the technology of bakery products for functional purposes using amaranth seed processing products from local raw materials.
Keywords: Amaranths; wheat flour; proteins